2016
DOI: 10.1128/iai.01347-15
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi CheD Promotes Various Functions in Chemotaxis and the Pathogenic Life Cycle of the Spirochete

Abstract: b Borrelia burgdorferi possesses a sophisticated chemotaxis signaling system; however, the roles of the majority of the chemotaxis proteins in the infectious life cycle have not yet been demonstrated. Specifically, the role of CheD during host colonization has not been demonstrated in any bacterium. Here, we systematically characterized the B. burgdorferi CheD homolog using genetics and biochemical and mouse-tick-mouse infection cycle studies. Bacillus subtilis CheD plays an important role in chemotaxis by dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
0
24
1
Order By: Relevance
“…3; Table 2). The ID 50 values for the wild-type and ⌬bb0318/pBSV2G bb0318 spirochetes identified in this experiment are slightly higher than those reported previously for the B31 A3 genetic background (28,44,46,47). Together, these data suggest that bb0318 promotes B. burgdorferi mammalian infectivity.…”
Section: Figcontrasting
confidence: 43%
“…3; Table 2). The ID 50 values for the wild-type and ⌬bb0318/pBSV2G bb0318 spirochetes identified in this experiment are slightly higher than those reported previously for the B31 A3 genetic background (28,44,46,47). Together, these data suggest that bb0318 promotes B. burgdorferi mammalian infectivity.…”
Section: Figcontrasting
confidence: 43%
“…In several species of pathogenic bacteria, the CheY response regulator has been shown to play an important role in chemotaxis, which is also needed for virulence (Butler and Camilli, ; McGee et al , ; Antunez‐Lamas et al , ; Lertsethtakarn et al , ). To date, only two studies have shown that chemotaxis – specifically involving the histidine kinase cheA2 and phosphatase enhancer cheD – is essential for the infectious life cycle of B. burgdorferi (Sze et al , ; Moon et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…At least three independent assays were performed. The chemotactic swarming ability of individual bacterial colonies of each strain was determined by plating no more than 50 cells into a 95-mm by 15-mm petri dish containing semisolid P-BSK diluted as described above (12,13). Plates were incubated for 4 weeks, at which time colony diameters were measured.…”
Section: Methodsmentioning
confidence: 99%
“…2A). A modified swarm plate assay was also performed to more accurately assess the chemotactic behavior of individual bacteria (12,13). The swarm plate assay is a group event where millions of bacteria attempt to migrate from the initial site of inoculation (in a semisolid plate) as they respond to chemotactic materials and metabolize neighboring nutrients, resulting in a swarm ring.…”
Section: Chey2 Response Regulator Affects Virulencementioning
confidence: 99%